Self-Determination Skills in Postsecondary Students with Learning Disabilities - Rasheed, Saleem A. (Journal of the American Academy of Special Education Professionals, 2008)
Many adult students with learning disabilities have entered postsecondary schools in recent years. Many of these students experience cognitive, emotional, and behavioral limitations that may act as obstacles in their educational processes and subsequent careers. Research has shown that self-determination skills can help ameliorate the effects of these limitations in secondary students. The purpose of this article is to investigate and to discuss the level and need of self-determination skills of students with learning disabilities who are enrolled in postsecondary education.